Enhancing student success through technology: Insights from recent doctoral research on community colleges - Basnet, Ganga B.; Williams, Cherryllynn; Bista, Rajendra (American Journal of STEM Education, 2025)
This study examines the role of technology in community colleges by analyzing recent doctoral dissertations from 2020 to 2024. A content analysis identified four key themes: the impact of technology on student retention, equity and accessibility challenges, integration in teaching and learning, and faculty professional development. Findings indicate that AI-driven tools, virtual learning environments, and adaptive technologies enhance student engagement and retention. However, disparities in technology access and faculty preparedness remain significant challenges. The study underscores the importance of targeted institutional strategies, such as digital literacy programs, professional development initiatives, and equitable technology policies, to bridge the digital divide. Recommendations focus on scalable technological interventions to support diverse student populations and strengthen institutional effectiveness in community college education.